Assiciation Between Inter-disciplinary Oral Diseases and General Well-being of the Patients: Quick Update or Curent Understanding - Margvelashvili-Malament , Mariam (Caucasus Journal of Health Sciences and Public Health, 2020)
Oral cavity has often been referred to as the “mirror of the body”, as many diseases manifest signs and symptoms in the mouth. Recently, the research interest has reversed and focused on the possible association between periodontal diseases and various systemic diseases and conditions. This presentation will provide a quick update on the association of periodontal diseases with cardiovascular diseases, respiratory diseases, rheumatoid arthritis, and cognitive impairment. It will also review the comorbidity factors related to the complete edentulism. The studies reveal relationship between periodontal disease and these systemic diseases. Additionally, the same diseases are linked to the complete edentulism. Whether this relationship is casual, or causal has yet to be determined. However, the lecture intends to raise the awareness among the patients and the healthcare providers of this possible association between periodontal diseases and the complete edentulism with chronic noncommunicable diseases. Health-care providers and caregivers need to be educated of long-term harmful outcomes of poor oral hygiene, periodontal disease, tooth extractions,